Raman microspectroscopic study for the detection of oral field cancerisation using brush biopsy samples. Issue 10 (30th July 2020) - Behl, Isha; Calado, Genecy; Vishwakarma, Anika; Flint, Stephen; Galvin, Sheila; Healy, Claire M.; Leite Pimentel, Marina; Malkin, Alison; Byrne, Hugh J.; Lyng, Fiona M.
Abstract: Field cancerisation (FC) is potentially an underlying cause of poor treatment outcomes of oral squamous cell carcinoma (OSCC). To explore the phenomenon using Raman microspectroscopy, brush biopsies from the buccal mucosa, tongue, gingiva and alveolus of healthy donors (n = 40) and from potentially malignant lesions (PML) of Dysplasia Clinic patients (n = 40) were examined. Contralateral normal samples (n = 38) were also collected from the patients. Raman spectra were acquired from the nucleus and cytoplasm of each cell, and subjected to partial least squares‐discriminant analysis (PLS‐DA). High discriminatory accuracy for donor and PML samples was achieved for both cytopalmic and nuclear data sets. Notably, contralateral normal (patient) samples were also accurately discriminated from donor samples and contralateral normal samples from patients with multiple lesions showed a similar spectral profile to PML samples, strongly indicating a FC effect. These findings support the potential of Raman microspectroscopy as a screening tool for PML using oral exfoliated cells. Abstract : The prognosis of oral cancer can be influenced by the potential of malignant transformation of tissues surrounding an original lesion‐ field cancerisation. It is demonstrated that Raman microspectroscopy of oral brush biopsy samples can identify this phenomenon with high accuracy, supporting its potential role in screening protocols for potentially malignant lesions.